2016
DOI: 10.17665/1676-4285.20165393
|View full text |Cite
|
Sign up to set email alerts
|

Capacidade para o trabalho da equipe de enfermagem hospitalar: estudo correlacional

Abstract: Aims:  to  evaluate  the  working  ability  of  a  hospital  nursing  team. Method: this is a descriptive and cross-sectional study. The subjects of the survey were 144  nursing  workers  from  a  federal  hospital.  Data  were  collected  through  the  Work Ability Index questionnaire and treated by descriptive and inferential statistical analysis. Results: the ability for work was evaluated as low for 3.5% of the workers, moderate for 20.8%,  good  for 47.2%  and  excellent  for 28.5%.  There  was  a  correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
1
0
2
Order By: Relevance
“…In Ethiopia, female nurses had multiple roles outside the workplace, such as care of their children. On another studies conducted in Slovakia, Brazil and Iran [ 40 42 ] showed that gender disparity had no effect on level of work ability. These differences could be due to methodological variation and national socio-cultural differences.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, female nurses had multiple roles outside the workplace, such as care of their children. On another studies conducted in Slovakia, Brazil and Iran [ 40 42 ] showed that gender disparity had no effect on level of work ability. These differences could be due to methodological variation and national socio-cultural differences.…”
Section: Discussionmentioning
confidence: 99%
“…Esses fatores, associados à complexidade das tarefas e, muitas vezes, a outros empregos, podem gerar, ao longo do tempo, desgaste das capacidades vitais do trabalhador, com consequências para o desenvolvimento de tarefas laborais. (2) Algumas pesquisas já demonstraram que após os 45 anos, o trabalhador encontra-se com maior vulnerabilidade a prejuízos na capacidade funcional física e mental, devido a alterações fisiológicas próprias do organismo, podendo ser agravadas pelo surgimento de patologias e outros processos. Assim, a variável idade constitui-se como importante contribuinte no processo de comprometimento da saúde do trabalhador, podendo incidir diretamente sobre a capacidade para o trabalho (CT).…”
Section: Introductionunclassified
“…(3,4) A capacidade para o trabalho pode ser conceituada como o bem-estar físico e mental do trabalhador, que o torna capaz de desenvolver o seu trabalho em função das demandas e de seu estado de saúde. (2) Na terceira idade, a atividade laboral tem sido apontada como importante mantenedora da identidade social e ferramenta para a promoção da saúde. (5) As condições de trabalho vivenciadas pela equipe de enfermagem têm ocasionado problemas de saúde, tendo como consequência os acidentes, o absenteísmo e o afastamento por doença, dificultando a organização do trabalho e, por conseguinte a qualidade da assistência de enfermagem prestada.…”
Section: Introductionunclassified